Update on Nutrition and Food Allergy - De Jong, Nicolette W.; Wichers, Harry J. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book describes the causes, diagnosis, and effects of food allergy. It goes deeper into the molecular and cellular mechanisms of food allergy and, in particular, into effects of the processing of certain nutrients, e.g., cow's milk on the allergenicity of proteins. The book also focuses on new nutrients, e.g., seaweed, and possible effects on allergy and inflammation.